2023
DOI: 10.1007/s12020-023-03305-x
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin induces ovarian cancer resistance to anoikis by regulating mitochondrial activity

Abstract: Purpose Ovarian cancer is characterized by recurrent peritoneal and distant metastasis. To survive in a non-adherent state, floating ovarian cancer spheroids develop mechanisms to resist anoikis. Moreover, ascitic fluid from ovarian cancer patients contains high levels of visfatin with anti-apoptotic properties. However, the mechanism by which visfatin induces anoikis resistance in ovarian cancer spheroids remains unknown. Here, we aimed to assess wheather visfatin which possess anti-apoptotic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Recent research found the regulation of mitochondrial activity can lead to ovarian cancer spheroids becoming resistant to anoikis. This finding suggests that targeting anoikis resistance may be a promising approach for treating peritoneal metastasis in SOC [ 22 ]. However, there is a lack of research examining the potential predictive significance of anoikis in SOC patients by using bioinformatics techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research found the regulation of mitochondrial activity can lead to ovarian cancer spheroids becoming resistant to anoikis. This finding suggests that targeting anoikis resistance may be a promising approach for treating peritoneal metastasis in SOC [ 22 ]. However, there is a lack of research examining the potential predictive significance of anoikis in SOC patients by using bioinformatics techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the components in the link between adipose tissue and the inflammatory response, but the mechanism has not been fully explored [92]. Research by Gogola-Mruk J. et al [100] demonstrates that visfatin acts as an anti-apoptotic factor by regulating mitochondrial activity, leading to resistance to anoikis in ovarian cancer spheroids. These findings suggest that visfatin is a potential new therapeutic target for the treatment of ovarian cancer with peritoneal dissemination [100].…”
Section: Visfatinmentioning
confidence: 99%
“…Research by Gogola-Mruk J. et al [100] demonstrates that visfatin acts as an anti-apoptotic factor by regulating mitochondrial activity, leading to resistance to anoikis in ovarian cancer spheroids. These findings suggest that visfatin is a potential new therapeutic target for the treatment of ovarian cancer with peritoneal dissemination [100]. Results from Nacarelli T. et al [101] suggest that NAMPT inhibitors (such as FK866) may be repurposed to suppress therapy-induced senescence-associated CSCs for improving platinum-based standard of care, a major obstacle in the clinical management of EOC [101].…”
Section: Visfatinmentioning
confidence: 99%
See 2 more Smart Citations